Palm oil mill secondary effluent (POMSE) treatment via photocatalysis process in presence of ZnO-PEG nanoparticles - Zainuri, Nur Zarifah; Hairom, Nur Hanis Hayati; Abu Bakar Sidik, Dilaelyana; Desa, Amira Liyana; Misdan, Nurasyikin; Yusof, Norhaniza; Mohammad, Abdul Wahab (Elsevier Ltd., 2018)
Palm oil mill secondary effluent (POMSE) has high colour intensity, turbidity and organic load of biochemical oxygen demand which still not achieved the discharged requirement by department of environment and led to detrimental to the aquatic life. Photocatalysis process is one of the promising method in wastewater treatment due to its advantages. This study reports on the POMSE treatment using photocatalysis process in presence of ZnO-polyethylene glycol (ZnO-PEG) nanoparticles. The characterization results using fourier-transform infrared spectroscopy, X-Ray diffraction and transmission electron microscopy show that there are no impurities present in the samples and presenting the nature and chemical bonds of ZnO-PEG besides having less agglomeration and smaller average in size (25–150 nm) compared to commercial ZnO (25–200 nm). ZnO-PEG nanoparticles have a great potential in degradation of POMSE and this is supported with the results obtained from the experimental works. Four potential factors which are different type of (A) photocatalysts, (B) pH of the POMSE, (C) ZnO-PEG loading and (D) concentration of POMSE were evaluated for the significance design of experiment. It is found that all the main factors were significant, with contributions of (A)66%, (B)73%, (C)84% and (D)84% respectively, to the POMSE degradation. Accordingly, the most favorable condition for the photocatalysis degradation process of POMSE is under pH 6.5 in presence of 0.5 g/L ZnO-PEG for the 50% of POMSE dilution. It is believed that this integrated approach can be implemented in the industry to achieve discharged standard of POMSE and maintain the green environment for future generation.